Assessing The Risk of Financial Failure And Market Power in Borsa Istanbul Healthcare Sector: An Analysis Based on Grover G, Zmijewski Z And Tobin's Q Models (Third Sector Social Economic Review, 2025)
With the impact of globalization and technological advancements, it is becoming increasingly difficult for businesses to maintain their competitive edge. Therefore, healthcare enterprises have become dependent on strong financial performance to access external financial resources. This study aims to evaluate the market power and risk of financial failure of 6 companies operating in the healthcare sector in Borsa Istanbul. For this purpose, the financial statements of healthcare companies listed on Borsa Istanbul for the period 2016-2024 are used, and the risk of financial failure is analyzed using the Grover-G and Zmijewski-Z models. Market power is analyzed using Tobin's Q ratio. This study makes a unique contribution to the literature by integrating the market-based Tobin's Q ratio in the financial failure analysis of companies operating in the healthcare sector, rather than relying only on traditional models. As a result of the study, the findings of the Grover G-Score, which is used to predict the risk of financial failure of healthcare firms, are largely consistent with the Zmijewski Z-Score and show that all firms have a financially sound structure throughout the analysis period. Moreover, the correlation matrix reveals a significant positive relationship between Grover G-Score and Tobin's Q ratio. This finding indicates that there is a strong link between the growth potential of companies and their market valuation and that companies with high growth potential are valued higher by the market.
Keywords: Health Sector; Financial Performance; Financial Failure; Financial Distress Prediction Models; Market Power